2016
DOI: 10.5409/wjcp.v5.i1.112
|View full text |Cite
|
Sign up to set email alerts
|

Dental knowledge and awareness among grandparents

Abstract: Oral hygiene and dietary habits are established during childhood. There is a great need for dental education of grandparents as they serve as role models for young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Grandparents are more involved in childrearing, not just because of extended longevity but also due to family structural changes (e.g., rises in lone-parent households) and socioeconomic trends (e.g., increases in financial difficulties) 23–25 . It was reported that grandparents hold poor knowledge of nutritional and oral hygiene requirements for children 26,27 , and children aged 1.6 years old and 3 years old living with or looked after by grandparents have been suggested to have increased risk of dental caries 14–17 , particularly in urban children 18 . However, the results are not always consistent in 4–5 year-old children 16 , and the effects in children who are more independent in self-care and whose deciduous teeth start to shed while permanent teeth start to grow (around 6–7 years old) are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Grandparents are more involved in childrearing, not just because of extended longevity but also due to family structural changes (e.g., rises in lone-parent households) and socioeconomic trends (e.g., increases in financial difficulties) 23–25 . It was reported that grandparents hold poor knowledge of nutritional and oral hygiene requirements for children 26,27 , and children aged 1.6 years old and 3 years old living with or looked after by grandparents have been suggested to have increased risk of dental caries 14–17 , particularly in urban children 18 . However, the results are not always consistent in 4–5 year-old children 16 , and the effects in children who are more independent in self-care and whose deciduous teeth start to shed while permanent teeth start to grow (around 6–7 years old) are unknown.…”
Section: Introductionmentioning
confidence: 99%